Morfologi Benih Dan Perkecambahan Pala (Myristica fragrans Houtt.) Sebagai Sumber Benih Di Hutan Rakyat, Pulau Bacan, Halmahera Selatan - Sulvia La Mente; Rusli Buamona; Muhammad Nur; Salam Salam; Saipul Riyadi; Laswi Irmayanti; Nurhikmah Nurhikmah (EnviroScienteae, 2020)
The development of nutmeg (Myristica fragrans Houtt) community forests needs to be supported by high-quality seed procurement, both physical, physiological, and genetic quality. Physically it can be done by morphological analysis in the form of length, diameter, and weight of seeds. Meanwhile, to determine the physiological quality, one of which is by observing germination. This research aimed to identify the morphology of seeds and germination of nutmeg (M. fragrans Houtt.) from different seed sources in the development of nutmeg community forests in Bacan, South Halmahera. The results showed that the morphology of nutmeg seeds in the shape, color, and skin surface variables at the three locations (Amasing, Papaloang, and Babang) obtained the same results, namely oval, brownish-black and shiny. Whereas in seed length, nutmeg from Papaloang has a longer seed size than seeds from Amasing and Babang. In the germination parameter values, seeds from Papaloang were found to have the highest value, namely the percentage of germination (K = 35%), peak value (PV = 0.56), average daily germination (MDG = 0.56), germination value (NK = 0.31 ).